Outcome and Safety of Different Cumulative Doses and Protocols of Intravenous Methylprednisolone in Moderate to Severe and Active Graves’ Ophthalmopathy - Amelya Permata Sari; M Sidik; Syntia Nusanti (Majalah Oftalmologi Indonesia, 2017)
Background: Graves’ ophthalmopathy (GO), also known as Graves’ orbitopathy or thyroid eye disease, has a potential sight-threatening complications. The activity and severity are important determinants in GO and are implications for treatment. Intravenous Glucocorticoid (GC) was associated with significantly greater efficacy and was better tolerated than oral route in the treatment of patients with moderate to severe and active GO. Intravenous GC has a variation cumulative dose and protocols; meanwhile the optimal treatment is still undefined. The aim of this literature review was to analyze the outcome and safety of different cumulative doses and protocols of intravenous methylprednisolone of patients with moderate to severe and active GO. Methods: The literature search was conducted from Google Scholar and Pubmed for journal articles that were published and related to the use of IVGC in moderate to severe and active GO Results: From the keywords mentioned, titles were screened for eligibility and seventeen articles were found. After being checked for the duplication, the articles were screened based on the abstracts and/or full texts. As many as eight articles met the inclusion criteria, others were excluded. Conclusion: Intravenous GC therapy in moderate to severe and active GO provide effect in reducing CAS, decreasing lid aperture size, decreasing proptosis size, and disappearing diplopia. A protocol uses a low cumulative doses (<5 g) of methylprednisolone weekly for 6 weeks and then halved dose weekly for another 6 weeks are preferred due to higher response in clinical outcome and safety profile.